Duality in Political Discourse: A Critical Analysis of the Constitutional Union Party in Morocco - Chaaibi, Sami; Marouane , Mohamed; Mokhtari, Najat (Integrated Journal for Research in Arts and Humanities, 2024)
This article critically examines the discourse of the Constitutional Union party (CU) in Morocco, focusing on uncovering discursive duality within its political communication. Drawing on Critical Discourse Studies, the study adopts Van Dijk’s (2008) mental model approach to illuminate the party’s ideological perspectives and evaluate its consistency with declared liberal principles, specifically investigating how liberalism is cognitively reflected in CU’s discourse. Through analysis of CU’s discursive strategies claimed to embody ideological connotations across political, economic, and gender issues, the study identifies linguistic anomalies that point to a divide between liberal and non-liberal elements in the party’s disseminated discourse. This observed linguistic duality prompts critical inquiries into the consistency of the party’s ideological stance throughout a variety of contexts, a fact that stresses the necessity for further exploration of the social legitimacy of Moroccan political parties in relation to their circulated discourse.